Dietary Fructose and Serum Hyperfructosemia in Obese Non-Insulin Dependent Diabetic SHR/NTUL//-Cp Rats - Tulp, Orien L; Anderson, Michael E.; Rizvi, A. A. (British Journal of Healthcare and Medical Research, 2023)
To determine the effects of a high fructose diet on key glycemic parameters in non-insulin dependent rats, groups of lean and obese SHR/Ntul//-cp rats were fed nutritionally complete, isoenergetic diets containing 54% carbohydrate (CHO, w/w) in which the CHO was in the form of cooked cornstarch (ST) or 27% ST plus 27% fructose (CSF) from one until 9 months of age. Measures of body weight (BW), combined fat pad mass (sum of epididymal, retroperitoneal and dorsal subcutaneous depots), glycated hemoglobin (GHB) and serum fructosamine (SFA) were obtained at the end of the study. Body weights of obese ST >> lean ST, and increased only modestly further in both phenotypes when fed the CSF diet; Combined fat pad mass of obese >>> lean and were minimally impacted by diet in either phenotype. Glycemic parameters including Fasting and OGT response plasma glucose, insulin and Insulin to Glucose ratio of Obese ST >> lean ST. GHB and SFA of obese ST > Lean ST, and the CSF diet increased GHB in lean and SFA in both phenotypes. These results indicate that partial substitution of Fructose for sucrose while exaggerating some parameters of NIDDM and chronic kidney disease (CKD), was neither beneficial or ameliorative in significantly attenuating the magnitude of NIDDM in the obese-NIDDM SHR/Ntul//-cp rat.